Leader Follower Tracking with Obstacle Avoidance using Circular Paths Algorithm - Rashid, Abdulmuttalib T. (Basrah Journal for Engineering Sciences, 2016)
This paper deals with a new algorithm called circular paths for leader follower tracking with obstacle avoidance using. In leader follower tracking, one robot acts as a leader with defined motion and the other robot acts as a follower which position itself in accordance with the position and orientation of the leader. The leader movement is dependent on an assigned trajectory and the follower movement is dependent on the circular paths algorithm. In each step, this algorithm constructs a circular path using three points represented by the next step position of the leader robot, the last step position and the current step position of the follower robot. The next position of the follower robot lays on the circumstance of the circular path and the orientation is represented by the tangent line to this circular path at this next position of the follower robot. When an obstacle intersect any circular path for the follower robot, then this path must be replaced by another circular path construct from the two positions of the follower robot and the leader position is replaced by the tangent point to the obstacle. Simulation results illustrate the soundness of this algorithm.